Fabrication and characterization of facilitated transport membrane for gas separation - Nasir, R. (Trans Tech Publications Ltd, 2014)
The new membrane material containing facilitate transport medium to enhance the performance of gas separation membrane has been fabricated by using monoethanolamine (MEA) as a fixed carrier with different concentration (5 & 10 wt. ) by using the solvent evaporation method. The developed membranes were characterized by using Field Emission Electron Microscope (FESEM), Fourier Transform Infrared (FTIR), and Thermo-Gravimetric Analysis (TGA). The developed membranes were found nonporous and dense in structure. Â© 2014 Trans Tech Publications, Switzerland.